Local Wisdom Using Onjhem to Catch Indian Scad (Decapterus Russelli) in Pasongsongan Waters (Sumenep-Madura Regency) and Surrounding Areas - Muhammad Zainuri; Mohamat Agus Masput (Journal of Social Science, 2022)
Onjhem is a fishing tool that has long been used by Pasongsongan fishermen to catch fish. The Onjhem function (read: onjem) is generally referred to by another name, namely rumpon (Indonesian)/ FADs (Fish Aggregating Device) to collect fish in a selected fishing area. Local wisdom has been maintained until now in the use of onjhems, namely by only choosing one of a number of onjhems placed in the sea. How the local wisdom with the preservation of Indian scad fish resources in the waters of Pasongsongan and its surroundings is the goal of this research. The method used for data analysis from 2015 to 2021, namely quantitative descriptive with an approach to technical, biological, and level of utilization aspects. The results showed that local wisdom in the use of Indian scad fishing aids in the form of onjhem can maintain the sustainability of the potential of these fish resources.